Collision‐induced thermochemistry of reactions of dissociation of glycyl–homopeptides—An experimental and theoretical analysis. Issue 2 (February 2017) - Ivanova, Bojidarka; Spiteller, Michael
Abstract: The research draws on experimental and theoretical data about energetics and kinetics of mass spectrometric (MS) reactions of glycyl homopenta– (G5 ) and glycyl homohexapeptides (G6 ). It shows the great applicability of the methods of quantum chemistry to predict MS profile of peptides using energetics of collision induced dissociation (CID) fragment species. Mass spectrometry is among irreplaceable methods, providing unambiguous qualitative, quantitative and structural information about analytes, applicable to many scientific areas like environmental chemistry; food chemistry; medicinal chemistry; and more. Our study could be considered of substantial interdisciplinary significance, where MS proteomics is widely used. The experimental design involves electrospray ionization (ESI) and CID MS/MS. Theoretical design is based on ab initio and density functional theory (DFT) methods. Experimental MS and theoretical free Gibbs energies as well as rate constants of fragment reactions are compared. The thermodynamic encompasses gas–phase and polar continuum analysis, including polar protic and aprotic solvents within temperature T  = 10–500 K; dielectric constant ε  = 0–78, pH, and ionic strengths μ  = 0.001–1.0 mol dm −1 . There are computed and discussed 39 protonated forms of peptides at amide N– and –(NHC)=O centers; corresponding fragment ions studying their thermodynamic stability depending on experimental conditions. A correlation analysis between molecular conformations of parent ions and fragment species; their proton accepting ability and internal energy distribution is carried out. Data about ionization potentials (IPs) and electron affinities (EAs) are discussed, as well.